Preparation of a Self-Lubricating Cu/h-BN Coating on Cemented Carbide - Tongkun Cao; Zhibin Zhu; Yajun Liu (Advances in Materials Science and Engineering)
In this work, a Cu/h-BN self-lubricating coating was prepared on cemented carbide by electrospark deposition (ESD). The microstructure and properties of the coating were examined. The results showed that no decomposition of or reactions with h-BN occurred. As the h-BN content and capacitance increased, the number of pores and microcracks in the coatings increased. Additionally, as the capacitance increased, the electrode mass loss increased. However, the specimen mass increased first and then decreased. The coating thickness was affected by the capacitance, deposition time, and volume ratio of h-BN to Cu. The results exhibited were consistent over the tests. The self-lubricating coating exhibited excellent tribological behavior under the test conditions, and the worn surface showed features consistent with shear slippage and abrasive wear.